Effects of bacterial organic selenium, selenium yeast and sodium selenite on antioxidant enzymes activity, serum biochemical parameters, and selenium concentration in Lohman brown-classic hens - Muhammad, A. I.; A. M., Dalia; Loh, T. C.; Akit, H.; Samsudin, Anjas A. (Springer Dordrecht, 2022)
This study compares the effects of sodium selenite, selenium yeast, and enriched bacterial organic selenium protein on antioxidant enzyme activity, serum biochemical profiles, and egg yolk, serum, and tissue selenium concentration in laying hens. In a 112-d experiment, 144 Lohman Brown Classic hens, 23-wks old were divided into four equal groups, each has six replicates. They were assigned to 4 treatments: 1) a basal diet (Con), 2) Con plus 0.3 mg/kg feed sodium selenite (SS); 3) Con plus 0.3 mg/kg feed Se-yeast (SY): 4) Con plus 0.3 mg/kg feed bacterial enriched organic Se protein (ADS18) from Stenotrophomonas maltophilia bacteria. On d 116, hens were euthanized (slaughtered) to obtain blood (serum), liver organ, and breast tissue to measure antioxidant enzyme activity, biochemical profiles, and selenium concentration. The results show that antioxidant enzyme activity of hens was increased when fed bacterial organic Se (ADS18), resulting in a significant (P < 0.05) increase in serum GSH-Px, SOD, and CAT activity compared to other treatment groups. However, ADS18 and SY supplementation increase (P < 0.05) hepatic TAC, GSH-Px, and CAT activity, unlike the SS and Con group. Similarly, dietary Se treatment reduced total cholesterol and serum triglycerides concentrations significantly (P < 0.05) compared to the Con group. At 16 and 18 weeks, selenium concentration in hen egg yolks supplemented with dietary Se was higher (P < 0.05) than in Con, with similar patterns in breast tissue and serum. Supplementation with bacterial organic Se (ADS18) improved antioxidant enzyme activity, decreased total serum cholesterol and serum lipids, and increased Se deposition in egg yolk, tissue, and serum. Hence, organic Se may be considered a viable source of Se in laying hens.